Esophageal striated muscle contractions in patients with Chagas' disease and idiopathic achalasia - Dantas,R.O. (2002)
Chagas' disease causes degeneration and reduction of the number of intrinsic neurons of the esophageal myenteric plexus, with consequent absent or partial lower esophageal sphincter relaxation and loss of peristalsis in the esophageal body. The impairment of esophageal motility is seen mainly in the distal smooth muscle region. There is no study about esophageal striated muscle contractions in the disease. In 81 patients with heartburn (44 with esophagitis) taken as controls, 51 patients with Chagas' disease (21 with esophageal dilatation) and 18 patients with idiopathic achalasia (11 with esophageal dilatation) we studied the amplitude, duration and area under the curve of esophageal proximal contractions. Using the manometric method and a continuous perfusion system we measured the esophageal striated muscle contractions 2 to 3 cm below the upper esophageal sphincter after swallows of a 5-ml bolus of water. There was no significant difference in striated muscle contractions between patients with heartburn and esophagitis and patients with heartburn without esophagitis. There was also no significant difference between patients with heartburn younger or older than 50 years or between men and women or in esophageal striated muscle contractions between patients with heartburn and Chagas' disease. The esophageal proximal amplitude of contractions was lower in patients with idiopathic achalasia than in patients with heartburn. In patients with Chagas' disease there was no significant difference between patients with esophageal dilatation and patients with normal esophageal diameter. Esophageal striated muscle contractions in patients with Chagas' disease have the same amplitude and duration as seen in patients with heartburn. Patients with idiopathic achalasia have a lower amplitude of contraction than patients with heartburn.